Negative Affect during a Collective (but Not an Individual) Task Is Associated with Holistic Attention in East Asian Cultural Context - Tominaga, Hitoshi; Uchida, Yukiko; Miyamoto, Yuri; Yamasaki, Teruo (Frontiers in Psychology, 2017)
Previous studies have suggested that individuals from East Asian cultures are more likely to show holistic attention - a pattern of attention that incorporates contextual information into focal stimuli - than individuals from North American cultures. Holistic attention is also prevalent in communities that require close cooperation. However, it is not yet known how cooperation is related to holistic attention. We theorized that holistic attention increases when people experience negative affect (e.g. worry, sadness, frustration) during collective tasks (but not during individual tasks) because negative affect in social contexts signals the existence of potential threats to social harmony, thus indicating a need to restore social harmony. To examine this hypothesis, an experiment was conducted in which participants performed a musical duet either with another participant (a collective task requiring cooperation), or individually with a computer (individual task). After the musical task, the Framed Line Task (FLT) was administered to examine their holistic attention. Participants also reported their emotional states both before and after the music task. Results suggested that negative affect in the collective task - but not the individual task - was positively correlated with a holistic pattern of attention. The function of negative affect in social contexts as motivation to restore relationships and how this enhances holistic attention is discussed. The moderating effect of social context on the cognitive effects of negative affect are also discussed.